2022
DOI: 10.24071/llt.v25i1.3690
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Preferences of Multimedia Resources in an Extensive Listening Program

Abstract: Extensive listening has gained popularity in the past few years due to its benefits for foreign/second language learning. It improves language learners’ listening skills in a less stressful way because they can choose topics based on their interest or do the activity simply for enjoyment. Also, in the implementation, students may choose any multimedia resources in extensive listening activities. In this descriptive study, students’ preferences of multimedia resources used in extensive listening activities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are several benefits of Extensive Listening, and these have been used by several researchers. It was found that extensive listening improved students' vocabulary increase, pronunciation, and grammar (Sholihah et al, 2018;Yudhiantara & Syihabuddin, 2023) and enhanced their understanding of utilizing emphasis, intonation and pronunciation accurately (Setyawan et al, 2022;Chang et al, 2019 ). Engaging in extensive listening for recreational purposes yields beneficial outcomes in terms of learners' enhancement of listening skills and growth of perceptual abilities (Öztürk & Tekin, 2019).…”
Section: Finding and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several benefits of Extensive Listening, and these have been used by several researchers. It was found that extensive listening improved students' vocabulary increase, pronunciation, and grammar (Sholihah et al, 2018;Yudhiantara & Syihabuddin, 2023) and enhanced their understanding of utilizing emphasis, intonation and pronunciation accurately (Setyawan et al, 2022;Chang et al, 2019 ). Engaging in extensive listening for recreational purposes yields beneficial outcomes in terms of learners' enhancement of listening skills and growth of perceptual abilities (Öztürk & Tekin, 2019).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…To begin with, extensive listening has proven to be instrumental in enhancing students' listening competence. Extensive listening enables students to better interact with audio-based educational resources such as learning materials (Kurniawati et al, 2023), multimedia (Setyawan et al, 2022), podcasts (Angelia & Juliaty, 2021;Gökmen, 2021;Gonulal, 2020;Hakobyan, 2023), YouTube (Pamuji & Setyarini, 2021;Saputra & Fatimah, 2018), and other platforms, thereby empowering them to assume responsibility for their own educational progress. Chang et al (2019) emphasize that frequent, successful, and enjoyable experiences can be a key factor in motivating learners to develop their own listening fluency.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…In this case, students can access a variety of audio material, including various accents, speech rates, topics, and genres. Students can choose from a wide selection of listening resources such as podcasts, interviews, radio programs, songs, films, TV shows, and audiobooks (Setyawan et al, 2022). By combining varied content, learners become familiar with the different linguistic contexts and cultural aspects of the language.…”
Section: Introductionmentioning
confidence: 99%